The financial reporting quality, choice of payment and due diligence auditor in M&As: evidence from China - Tang, Jie (2018)
This dissertation contains three essays that examine the relationship between Chinese acquiring firms’ financial reporting quality, payment methods, auditor’s industry specialisation and their domestic merger and acquisitions (M&As) short-term performance (measured by CARs) and long-term performance (measured by ROA/ROE). As the result of its remarkable economic growth rate and admission to the World Trade Organisation (WTO), China has witnessed a dramatic increase of M&A activities over the past two decades. However, despite the vast amount of research on M&As, little has been produced about the area of China. Considering the impact of China’s economy as the second biggest in the world as well as the unique nature of Chinese institutions, more research should be done and it is the aim of this paper to enrich the literature in this area. It is hoped that the conclusions drawn from this research will be of interest to both market regulators and participants. The first essay examines the relationship of the acquiring firm’s financial reporting quality, payment method and their M&A performance in a sample of domestic M&As between unrelated parties. The results show that there is a significantly positive market reaction to acquisitions with high financial reporting quality, and acquirers with high financial reporting quality tend to choose stock involved payment. The research also shows that lower financial reporting quality acquiring firms tend to pay a higher premium to the target, which might be for compensating them for accepting stock payment. The second essay examines the relationship of the acquiring firm’s financial reporting quality, payment method and their M&A performance in a sample of domestic M&As between related parties. Since China still adopts two accounting approaches (purchase and pooling of interests) for business combination, there would be concern that acquiring firms would like to try to manipulate to adopt a certain approach. The research does not show that significant discretionary accruals difference between the firms for two approaches. However, it shows that when transactions are among related parties, because of less information asymmetry, there would be less likely of accrual manipulation. Furthermore, the distinction of the common control and uncommon control (as the criteria for applying accounting methods) imply the possibility that under common control there would be concern of tunnelling and M&As in cash payment would have more concern on this. The market response to the cash payments confirms this. The third essay examines the relationship acquiring firms’ financial reporting quality, auditor industry specialisation and their unrelated-party M&A performance. Since financial reporting quality is very important for investment decisions, financial reporting auditors also plays an important role. Also, when the involved parties are unrelated, the auditors are getting more important. Hence, the choice of due diligence auditor is very important to the acquiring firms. China allows listed companies to use same auditor to provide due diligence services. The research shows that when financial reporting auditors are industrial experienced, the acquiring firms are less likely to appoint a new auditor for due diligence. Also, when acquiring firms appoint a new auditor for due diligence, the market would not have significant response; however, when they appoint a new auditor with good industry experience, the market response positively. In summary, the three essays try to show in a developing market with transparency problem, there are some information asymmetry mediators, like financial reporting quality, payment methods choices and auditor/due diligence services; and also try to show how they work together and how they work to the M&As short-term and long-term performance. The following chapter explains the background and motivation of the research and introduces the contribution of the work to the existing body of knowledge.